Peripheral nerve injuries in baseball players - Cummins, C. A.; Schneider, D. S. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Baseball players place significant stress across their shoulders and elbows during the throwing motion, causing unique patterns of injuries in the overhead throwing athlete. Specific nerve injuries include suprascapular neuropathy, quadrilateral space syndrome, and cubital tunnel syndrome. Nonoperative treatment includes cessation of throwing and symptom management. As symptoms improve, athletes should start rehabilitation, focusing on restoring shoulder and trunk flexibility and strength. The final rehabilitation phase involves an interval throwing program with attention directed at proper mechanics, with the goal of returning the athlete to competitive throwing. Surgery may assist in a positive outcome in particular patients who fail to improve with nonoperative treatment. Additional indications for surgery may include more profound neuropathy and nerve compression by a mass lesion.